汉语课堂答问评价的现状及策略研究—以坤甸 MARANATHA 高中二年级学生为例 - Yunita, Yunita; Weniyanti, Weniyanti (Confucius Institute Universitas Sebelas Maret, 2024)
Classroom questioning and assessment are important components of classroom interaction and are also crucial in Chinese language teaching. However, in actual classroom teaching, most Chinese language teachers fail to understand the importance of student questioning and assessment. As a result, classroom teaching fails to achieve good results, to some extent diminishing students' interest in learning Chinese. This paper takes 96 students from the second grade of CHRISTIAN MARANATHA High School, divided into 24 students from class XI MIA, 36 students from class XI IIS 1, and 36 students from class XI IIS 2, as research subjects to investigate the current situation of classroom question and answer evaluation in high school and to propose relevant teaching strategies for classroom question and answer evaluation. This study mainly uses classroom observation, questionnaire survey, and interviews to analyze the current situation and strategies of classroom questioning and assessment. The survey results show that the current situation of classroom questioning and assessment for the second-year students at Pontianak MARANATHA High School includes seven aspects, analyzed in terms of the form of questions posed by teachers, the objects of assessment, the subjects of assessment, the timing of assessment, the content of assessment, the effectiveness of assessment, and the methods of assessment. Mainly, it includes: teachers often pose questions that focus on memory; the objects are mostly the teachers themselves, and opportunities for students to be assessed in classroom questioning are not profound; teachers mostly assess individuals; teachers' assessments are mostly direct; teachers pay more attention to the learning process and knowledge skills; questions posed by teachers mostly have a positive impact; and teachers mostly use oral language for classroom questioning assessment. The author hopes that this research will provide guidance and assistance for Chinese language teaching at CHRISTIAN MARANATHA High School. It analyzes the existing problems in classroom question and answer evaluation and proposes relevant teaching strategies based on theoretical guidance and classroom standards. These strategies aim to help teachers better understand the importance of classroom question and answer evaluation, continually enhance their evaluation capabilities, and promote the overall development of students' abilities. Additionally, it can serve as a reference for Chinese language classroom question and answer evaluations in other high schools.